The demand for and the supply of fuel efficiency in models of industrial organisation - Johannes Van Biesebroeck (Organisation for Economic Co-operation and Development (OECD), Joint Transport Research Centre (JTRC), 2010)
This report organizes and discusses empirical estimates of the effects of fuel prices and fuel emission standards on consumer and firm behaviour. I touch only briefly on model-free estimates. The focus is on results based on explicit models, taken mostly from the industrial organization literature. First, I review studies that identify the willingness to pay for fuel efficiency using static and dynamic models of vehicle demand. Next, I take explicitly into account that firms will adjust their product portfolios and the characteristics of the vehicles they offer. These decisions will have an impact on the choice set from which consumer demand is estimated and on the trade-off that consumers face between fuel efficiency and other desirable characteristics. Finally, I discuss models where firms choose to invest in innovations to achieve fuel efficiency gains without sacrificing characteristics.
Keywords: 330; Kraftstoff; Nachfrage; Konsumentenverhalten; Industrieökonomik